Pushing through or slacking off? Heterogeneity in the reaction to rank feedback - Florian Hett; Felix Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper studies heterogeneity in the reaction to rank feedback. In a laboratory experiment, individuals take part in a series of dynamic real-effort contests with intermediate feedback. To solve the identification problem in estimating the causal effect of rank feedback on subsequent effort provision we implement a random multiplier in the first round of each contest. The realization of this multiplier then serves as a valid instrument for rank feedback. While rank feedback has a robust effect on subsequent effort provision on average, an explicit analysis of between-subject heterogeneity reveals that a substantial fraction of participants in fact react entirely opposite than the aggregated results indicate. We further show that this heterogeneity has consequences for overall outcomes, thereby arguing that heterogeneous sensitivities to rank feedback could have implications for the design of various policies in education and organizations.
urn:nbn:de:hebis:30:3-466694
Keywords: C91; 330; heterogeneity; competitiveness; contest; rank feedback; relative performance evaluation